Traffic Control of Bacteria-Derived Molecules: A New System of Host-Bacterial Crosstalk - Hiroaki Konishi; Mikihiro Fujiya; Yutaka Kohgo (International Journal of Cell Biology)
Virulent microorganisms, such as pathogenic bacteria and viruses, are recognized by pattern recognition receptors (PRRs), including toll-like receptors (TLRs) and nucleotide-binding oligomerization-domain proteins (NODs), and induce inflammatory responses in mammalian hosts. Conversely, commensal bacteria and probiotics, which symbiotically confer health benefits on the host organisms, can lodge in the host intestinal tract without inducing intestinal inflammation. Recent advances in investigations concerning host-microbial interactions have shown that some effector molecules secreted from beneficial bacteria activate cell survival pathways, such as those mediated by p38 MAPK and Akt, and bring health benefits to mammalian hosts. It is noteworthy that such bacteria-derived molecules are taken into the intestinal epithelia through a transport or endocytosis system, thereafter exhibiting their beneficial effects. Understanding this traffic control process can aid in the comprehension of host and microbe interactions and may provide new insight to clarify the pathogenesis of intestinal disorders. This paper highlights the intestinal trafficking systems of bacteria-derived molecules that affect the bacterial functions and modulate epithelial signaling cascades. The latter mechanism may contribute to the maintenance of intestinal homeostasis by improving the host damage induced by virulence factors and various disease states.